A new species of Heteroparasitus Juvara-Bals 1975 from Karavanke, Austria (Acari: Parasitidae) - Witaliński, Wojciech (Zootaxa, 2008)
A new mite species Heteroparasitus (Heteroparasitus) mariae sp. nov. (Acari: Parasitidae) is described from southern Austria (Karavanke Mountains). A key to the four known species in the genus is given, and the definition of the genus is revised.